A scoping review of the use of traditional medicine for the management of ailments in West Africa. - Selassi A D'Almeida; Sahr E Gbomor; Brima Osaio-Kamara; Mobolaji Timothy Olagunju; Olunike Rebecca Abodunrin; Morẹnikẹ Oluwátóyìn Foláyan (PLoS ONE)
Background The coexistence of traditional healing practices deeply rooted in cultural and historical contexts and the evolving landscape of modern healthcare approaches in West African societies creates a dynamic interplay between tradition and modernity in healthcare. This study aims to comprehensively map the landscape of traditional medicine use for health in West Africa. Methods A scoping review was conducted following the Joanna Briggs Institute (JBI) methodology and reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) guidelines. Research questions focused on the links between traditional medicine practices and health in West Africa. The systematic literature search covered PubMed, Web of Science, and CINAHL from database inception to September 2023. A descriptive analysis was conducted highlighting the years of publication, countries of publication, study designs of plant families and plant parts used for making traditional medicines, and the diseases the traditional remedies are for. Results The search identified 3484 records, with 46 articles meeting the inclusion criteria. Publications spanned from 1979 to 2023, with no observed trend in the number of publications over successive decades. Nigeria had the highest number of publications (54.3%), followed by Ghana (19.6%). The studies employed various designs, including clinical trials, ethnobotanical, ethnopharmacological, and experimental designs. Plant families frequently studied included Combretaceae, Euphorbiaceae, and Rubiaceae. Traditional remedies address various health issues, highlighting their versatility, from general symptoms to specific diseases. Conclusion This scoping review offers an extensive overview of traditional healing practices in West Africa. The studies highlighted in this review stress the necessity for culturally sensitive healthcare interventions. The widespread use of traditional medicine and the variety of practices underscore the importance of encouraging collaboration between traditional healers and modern healthcare professionals. This review also identifies knowledge gaps and areas needing further research, setting the stage for future exploration into West Africa's intricate healthcare landscape.